Implementation Of Esther's Leadership In Christian Leadership Profession - Debora Sitohang; Andar Gunawan Pasaribu; Ova Eniwati Habayahan; Devisere Nadeak (International Perspectives in Christian Education and Philosophy, 2024)
Women's leadership is nothing new in this modern era but has always been an interesting issue to discuss. The Bible records that Esther was a Jewish woman who was later appointed Queen of Persia to replace Vashti who then fought as leader for her Jewish people. The research method used is a qualitative method with literature research and Old Testament studies to clearly understand Esther's leadership style which can be applied in the current era of emancipation and Christian leadership. The research results show that Esther is able to become a heroic leader, supported by her excellent ability to communicate verbally and non-verbally.